Bersatu Lawan Api : Menanamkan Nilai Tanggap Bencana Sejak Usia Dini Melalui Psikogame yang Interaktif - Najwa Maharani Zahra; Nurul Huda Nabillah; Zabrina Zabrina; Nabila Asyifa; Dian Hamama; Devi Lusiria (INDO PUBLISHING, 2026)
Fire is a non-natural disaster that has a major impact, especially in developing countries like Indonesia. Early childhood is a vulnerable group, but has not received much education on appropriate disaster mitigation. This study developed an educational game “Pahlawan Cilik” to introduce fire mitigation to children aged 4–6 years. The method used was pre-experimental with a one-group pretest-posttest model. The results showed an increase in children's understanding after participating in the game. This game is effective because it involves visual, motoric, and emotional aspects in the learning process.